2021
DOI: 10.1111/jfpp.15640
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining fermentable sugars and fiber concentrate from asparagus by‐product

Abstract: In this study, different solid-liquid extraction conditions to obtain fermentable sugars from an asparagus by-product were investigated to produce a fiber concentrate.To evaluate the effects of agitation, solvent:sample ratio and temperature, an experimental design was used and the maximum extraction conditions of reducing sugars (RS) were determined. The diffusion coefficient of sugars in water at different temperatures was obtained, as well as the thermodynamic parameters of the process. The materials obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Methods that can be used to purify the protein meal include alcohol precipitation, isoelectric precipitation, and alkaline solution with isoelectric precipitation. Previous researchers have reported that the functional properties of agricultural products could be affected by various treatment methods (De Paula Laidens et al, 2021;Iwassa et al, 2019;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Methods that can be used to purify the protein meal include alcohol precipitation, isoelectric precipitation, and alkaline solution with isoelectric precipitation. Previous researchers have reported that the functional properties of agricultural products could be affected by various treatment methods (De Paula Laidens et al, 2021;Iwassa et al, 2019;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Asparagus ( Asparagus officinalis L.), as a perennial herb, is widely grown in many countries of its high value of rich in protein, vitamins and mineral elements (Laidens et al., 2021; Romojaro et al., 2013). As a health care vegetable, there were about ninety‐four compounds identified from asparagus (Jiménez‐Sánchez et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…
Asparagus (Asparagus officinalis L.), as a perennial herb, is widely grown in many countries of its high value of rich in protein, vitamins and mineral elements (Laidens et al, 2021;Romojaro et al, 2013).As a health care vegetable, there were about ninety-four compounds identified from asparagus (Jiménez-Sánchez et al, 2016).Asparagus contains some bioactive phytochemicals as polysaccharides, saponins, flavonoids, dietary fiber et al, which has an important role in health care including reducing blood lipids (Abdelrahman
…”
mentioning
confidence: 99%
See 1 more Smart Citation